Communication plan: a good instrument for a successful campaign. - Páez, Paola; Rodríguez, Ligia (Agronomía Mesoamericana, 2004)
The methodology used to design a communication plan for a Campaign to increase bean consumption in a Costa Rican urban community is described in this article. Results of an initial assessment, complemented with behavior tests, were the input used to obtain the preliminary information necessary to generate main ideas for the messages to be disseminated throughout the population. The communication plan (Version I) was designed based on this information and on conditions previously established by the Project. On the other hand, the contents for messages were drawn up, tested, and integrated into the plan, based on the main ideas. Then, the final communication plan (Version II) was the result of a group analysis. The process to design the communication plan is described emphasizing on the importance of team work and the direct knowledge of the population under study. The communication plan is a fundamental instrument to plan, implement, and evaluate the Campaign.